Exploring regional and gender disparities in Beninese primary school attendance: A multilevel approach - Kyle McNabb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This study combines household survey data from the Beninese Demographic and Health Survey with school supply statistics in order to investigate regional and gender disparities in primary school attendance rates in Benin. Despite almost unparalleled increases in enrolment since the 1990s, Benin remains virtually ignored in the literature surveying school attendance. Results of a logistic regression model highlight the important role played by factors such as household wealth and religion and show that, despite progress, gender disparities in education persist in Benin. The opportunity cost of attending school is also investigated and, in order to account for regional disparities in attendance, a multilevel model is estimated; results from a random slopes model highlight those communes where reductions in the cost of schooling could see the greatest improvements in attendance rates.
Keywords: I25; O12; I21; 330; economic development; demand for schooling; Africa; school attendance; multilevel model; Viet Nam